(untitled) (Medico Legal Update, 2020)
An approach to synthesizing silver nanoparticles(AgNPs)using a Fusarium graminarum fungus was established in the present study.These nanoparticles are identified with the following techniques to confirm the form, size, and other physical properties of the crystal:UV-Visible Spectroscopy(UV-Vis),where the AgNPs showed absorbance at 420 nm, while X-Ray Diffraction (XRD)showed diffraction peaks at(38.05°,4 nm).The experiment consisted of 40 mice divided into two groups, the first group of 20 mice was considered to be the control animals and the other group 20mice was 21day of treatment with a dose of AgNPs(0.1ml/ day).Microscopic examination of the kidney section showed lobulated glomeruli,a large area of hemorrhage, changes in degeneration, and inflammatory cell infiltration. Biometric changes of the renal corpuscle showed no significant difference between the study group,while Bowman’s capsule,Proximal,and distal convoluted tubules revealed increased significant differences between the two groups.